A Scalable One-Step Method for Synthesizing Durable Defect-Minimized Graphite-Metal Catalysts for Sustained Engineering Applications - Cao, Mengbo; Gao, Ming; Wei, Xingyue; Zhang, Hanmin (Environmental science & technology, 2025)
Catalytic oxidation is a key method for industrial decontamination, but it suffers from low electrical conductivity and unstable catalysts. Metal-stably bonded conductive network carbon composites show great potential, while their acquisition is costly and energy-intensive. By utilizing in situ redox reactions at a gram-scale, this study directly converts biomass fibers and copper precursors into a robust metal-bonded, defect-minimized graphite framework at 80 °C, enhancing its potential for sustainable engineering applications. When deployed as a fixed-bed reactor, the engineered catalyst demonstrates unprecedented operational stability, maintaining >99% contaminant removal efficiency during 21-day operation (flow rate: ∼8000 L h–1 m–2; hydraulic retention time: 37.3 s). Scalability analysis reveals a remarkable monthly processing capacity of 18,086 tons at an operational cost of 1.25 CNY/tonrepresenting an order-of-magnitude reduction compared to conventional industrial systems (30–60 CNY/ton). The high conductivity, stability, and adaptability complements its excellent performance, and the method can also be extended to other metals (e.g., Fe, Co) with similarly low energy requirements. The mild conditions of our synthesis method, coupled with the high stability performance, offer a sustainable oxidation decontamination route that nearly reaches the theoretical minimum energy consumption.